Pemanfaatan Aplikasi Tumblr dalam Pembelajaran Menulis Teks Anekdot Berbasis Ekologi pada Siswa Kelas 10 SMAN 1 Galis Pamekasan - Ricky Dwi Agus Bachtiar; Aflahah Aflahah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
In today’s digital era, utilizing information and communication technology in the learnig process is very useful to support quality learning. One of the learning innovation that attracts attention and is relevant to anecdoce text material is the Tumblr application. This study aims to describe the application of Tumblr application and the results of applying Tumblr application in the learning process. This type of research is qualitative by using descriptive method. The data collection techniques used include observation, interviews, and documentation. In this study, the data were analyzed through three stages, namelt condensing data, presenting data, and drawing conclusions. The results of this research is that there are five steps when implementing the Tumblr application. Meanwhile, the results of applying the Tumblr application in the learning process show that students can apply the Tumblr well, combine elements of humor with themes, improve anecdotal text writing skill, realize the importance of preserving the environment, and create a collaborative learning atmosphere.